Pengembangan Media Pembelajaran Interaktif Berbasis Mobile Learning untuk Meningkatkan Keterampilan Literasi Siswa, Media Pembelajaran, dan Kebugaran Jasmani - Nur Kumala, Azizah; Jasiah, Jasiah (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to develop mobile learning-based instructional media for physical fitness activities. The research and development method employed in this study follows a Research and Development approach. The subjects were Grade X students. Data collection instruments included observation and questionnaires. The data analysis technique used in this research involved descriptive percentages to process qualitative and quantitative data. This study underwent validation by two experts: one expert in physical fitness and one media expert, yielding average percentages of 100% for the physical fitness expert, 96% for the media expert, and 90% for the group trial. Hence, the product was deemed feasible and valid for use. Furthermore, product effectiveness testing resulted in a score of 83%, efficiency testing recorded a time of 29 minutes, and product attractiveness testing achieved a percentage of 83%. In conclusion, the mobile learning-based physical fitness instructional media, supported by these results, is categorized as excellent. Therefore, the developed product can be utilized effectively in the teaching and training processes.